Interpretasi Aci Usaba Sumbu dalam Karya Seni Lukis - Silasana, I Putu Arya; Budiaprilliana, Luh; Mudana, I Wayan (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2023)
The creation of works in the Independent Study MBKM program in this paper takes ideas or ideas about the interpretation of Aci Usaba Sumbu in Pakraman Timbrah Village in works of painting. The phenomenon of a religious ritual in Timbrah Village called Aci Usaba Sumbu which has its own uniqueness from the ceremonial facilities used in these religious activities. Banten Sumbu, which resembles a towering tower and the banten be guling which is offered by local villagers, is unique from a visual standpoint. The objects at the ceremony have their own meaning, the creator interprets them into life and social values through works of painting. The process of creating this work adopts the theory and methods of Alma M Hawkins. The creation method goes through 3 (three) stages, namely, the exploration, improvisation, forming stages. In the embodiment of the work, the ideas obtained created 6 works entitled: : 1) “Pengendalian Diri” , 2)”Keharmonisan” , 3)”Penyatuan”, 4)”Tri Kaya Parisudha”, 5)”Pohon Sumbu” 6)”Naga Sumbu”. The works created are a form of interpretation of Aci Usaba Sumbu along with the objects contained in the ceremony. With the creation of these works, it is hoped that they will be able to convey a message about the turbulence of the creator's feelings that have been observed.